Rheological characterization and safety evaluation of non-ionic lamellar liquid crystalline systems containing retinyl palmitate - Chorilli, Marlus [UNESP]; Rigon, Roberta B. [UNESP]; Calixto, Giovana [UNESP]; Cartezani, Pedro M.F. [UNESP]; Ribeiro, Maria C.A.P.; Polacow, Maria L.O.; Cerri, Paulo Sérgio [UNESP]; Sarmento, Victor H.V.; Scarpa, Maria Virgínia [UNESP] (American Scientific Publishers, 2016)
Retinyl palmitate (RP) is widely used as a special interest ingredient in dermatological formulations to improve the elasticity of the skin and to reduce wrinkles by stimulating collagen synthesis. Nanotechnology-based drug delivery systems, such as liquid crystalline systems (LCSs), can modulate drug permeation into skin and improve the drug action. The effects of such systems on the skin, however, are not completely known. Possible undesirable effects of these formulations on the skin can be detected and interpreted by histopathology and histomorphometry. The objective of this study was to perform a rheological characterization to evaluate the safety of RP used in a lamellar LCS in vitro and in vivo. LCSs containing polyether functional siloxane as a surfactant, silicon glycol copolymer as an oil phase and water at ratios of 60:10:30 and 40:30:30, with (F1v and F2v , respectively) and without (F1 and F2 respectively) RP, were investigated. The rheological characterization was performed using steady shear rate sweep tests and dynamic frequency sweep tests carried out for up to 30 days for various storage temperature conditions (25±2 °C, 37±2 °C and 5±2 °C). Cytotoxic effects were evaluated using J-774 mouse macrophages as a cellular model system. The in vivo tests were conducted on rabbits that had areas of skin treated as follows for 15 days: C (Control); F1; F1v; F2; and F2v. Histomorphometric and histopathological techniques were used to estimate the thicknesses of the epidermis and stratum corneum and the numbers of fibroblasts and leukocytes in the papillary dermis. Mean values were compared by ANOVA, followed by the Tukey test (p <0 05). The steady shear rate sweep and dynamic frequency sweep tests confirmed the high viscosity of the LCS and the typical pseudo-plastic characteristic of the lamellar system. The RP-unloaded LCS and the RP-loaded LCS did not produce cytotoxicity, nor did they provoke significant thickening of the epidermis and stratum corneum. The number of leukocytes in the treated areas did not change; however, the number of fibroblasts in the area treated with F1v was higher than in the areas treated with the control and F2. The histological analyses demonstrated that none of the formulations irritated the skin and that formulation F1v significantly increased the number of fibroblasts in the dermis, which could result in an increase in the production of collagen.
Keywords: Liquid-Crystalline Systems; Retinyl Palmitate; Rheological Characterization; Safety Evaluation; Skin